Characterization of E-cigarette coil temperature and toxic metal analysis by infrared temperature sensing and scanning electron microscopy – energy-dispersive X-ray. (5th December 2020) - Mulder, Haley A.; Stewart, James B.; Blue, Ivy P.; Krakowiak, Rose I.; Patterson, Jesse L.; Karin, Kimberly N.; Royals, Jasmynne M.; DuPont, Alexandra C.; Forsythe, Kaitlin E.; Poklis, Justin L.; Poklis, Alphonse; Butler, Shelle N.; et al.
Abstract: Introduction: Electronic cigarettes (e-cigarettes) have rapidly evolved since their introduction to the U.S. market. The rebuildable atomizer (RBA) offers user-driven modification to the heating element (coil) and wicking systems. Different coil materials can be chosen based on user needs and preferences. However, the heating element of an e-cigarette is believed to be one-source for toxic metal exposure. Methods: E-cigarette coils from Kanthal and nichrome wires were constructed in a contact and non-contact configuration and heated at four voltages. The maximum temperatures of the coils were measured by infrared temperature sensing when dry and when saturated with 100% vegetable glycerin or 100% propylene glycol. The metal composition of each coil was analyzed with Scanning Electron Microscopy-Energy-Dispersive X-Ray (SEM-EDX) when new, and subsequently after 1, 50, and 150 heat cycles when dry. Results: The coils reached temperatures above 1000 °C when dry, but were below 300 °C in both liquid-saturated mediums. Metal analysis showed a decrease of 9–19% chromium and 39–58% iron in Kanthal wire and a decrease of 12–14% iron and 39–43% nickel in nichrome wire after 150 heat cycles. Significant metal loss was observed after one heat cycle for both coil alloys and configurations. Conclusions: The loss of metals from these heat cycles further suggests that the metals from the coils are potentially entering the aerosol of the e-cigarette, which can be inhaled by the user.